Motivation, barriers and preferences of lifestyle changes among older adults with frailty and mild cognitive impairments: A scoping review of qualitative analysis. - Jamilah Mohammad Hanipah; Arimi Fitri Mat Ludin; Devinder Kaur Ajit Singh; Ponnusamy Subramaniam; Suzana Shahar (PLoS ONE)
Lifestyle intervention has proven effective in managing older adults' frailty and mild cognitive impairment issues. What remains unclear is how best to encourage lifestyle changes among older adults with frailty and Mild Cognitive Impairment (MCI). We conducted searches in electronic literature searches such as PubMed, Scopus, Cochrane Reviews, ProQuest, and grey resources to find articles published in English between January 2010 and October 2023. This review focused on research using a qualitative study design. We extracted data on publication year, location, the aim of the study, study population, involved intervention, barriers, motivations, and preferences reported in the articles. Out of 5226 retrieved, 253 articles were selected after the deletion of duplicates, title, abstract screening, and. We included fourteen articles for final analysis at the end of the review process. The two main themes generated from this review are intrinsic and extrinsic factors in motivations and barriers to lifestyle changes. The most reported motivators were the perceived benefits of lifestyle intervention and self-efficacy. Among the obstacles participants face are perceived adverse effects of intervention, lack of knowledge, existing impairment (physical or mental), and social support. Lifestyle change motivations and barriers among older adults mainly were intrinsic factors such as the perceived benefit of the intervention, self-efficacy, knowledge, familial commitment, and existing impairments. There is a need to empower older adults to overcome the barriers with support from healthcare professionals, the community, and the family.